Education effects on the medication adherence level in type 2 dm patients - Imas Masliyah; Dayan Hisni; Nita Sukamti (Institute of Computer Science (IOCS), 2023)
Education is the primary basis for the perfect treatment and prevention of Diabetes Mellitus. Minimum knowledge about Diabetes Mellitus will lead to complications more quickly, burdening the family and society. This research design is experimental research with a Quasi-Experimental Design in the form of a